2002
DOI: 10.1007/s001920200063
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Neck Mobility and Urethral Closure Pressure as Predictors of Genuine Stress Incontinence

Abstract: Two hundred and seventy-five consecutive patients with symptoms of lower urinary tract dysfunction underwent urodynamic evaluation, including multichannel urodynamics, urethral pressure profilometry, X-ray and ultrasound imaging. After women with previous incontinence or prolapse surgery or pelvic radiotherapy and those with evidence of urethral kinking on ultrasound had been excluded, 179 datasets were analyzed. Both bladder neck descent ( P<0.0001) and maximum urethral closure pressure ( P<0.0001) were stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 20 publications
3
52
1
7
Order By: Relevance
“…After removing variance due to measurement error, heritabilities of .80 and .64 were found for elbow and bladder mobility respectively. As measures of pelvic organ and joint mobility have previously been associated with disorders such as genital prolapse and incontinence (Dietz et al, 2002;Norton et al, 1995;Tincello et al, 2002), the present study supports the proposal that genetic influence may play a role in these disorders. Furthermore, the genetic association found between elbow and bladder mobility latent factors suggests the possibility of a genetically influenced mechanism, common to both pelvic organ and elbow mobility, which may play a small role in predisposing individuals to developing genital prolapse and incontinence.…”
Section: Discussionsupporting
confidence: 88%
“…After removing variance due to measurement error, heritabilities of .80 and .64 were found for elbow and bladder mobility respectively. As measures of pelvic organ and joint mobility have previously been associated with disorders such as genital prolapse and incontinence (Dietz et al, 2002;Norton et al, 1995;Tincello et al, 2002), the present study supports the proposal that genetic influence may play a role in these disorders. Furthermore, the genetic association found between elbow and bladder mobility latent factors suggests the possibility of a genetically influenced mechanism, common to both pelvic organ and elbow mobility, which may play a small role in predisposing individuals to developing genital prolapse and incontinence.…”
Section: Discussionsupporting
confidence: 88%
“…6,7,12,13 Dietz et al 14 investigated tape position and mobility after TVT placement and correlated these data with symptoms of incontinence. They found marked variation in position and mobility of the TVT relative to bladder neck and symphysis pubis and concluded that the success of the TVT is largely independent of the exact position it is left in.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not specifically evaluate urethral mobility, a subject to be reported in a separate study, our results indicate that the mobility detected at the level of the ARA may be consistent and comparable with observations of urethral mobility. Ultrasound scanning by tracking bladder neck motion (Dietz et al 2002;Pregazzi et al 2002;Schaer et al 1999) is a well-established means of obtaining dynamic images of the lower urinary tract, can be readily combined with the visualization of the ARA to acquire a better understanding of mechanism of the urinary continence of the whole pelvic floor.…”
Section: Discussion and Summarymentioning
confidence: 99%